Development of E-Module Based on E-Pub Plant Structure and Development Courses as Teaching Material to Improve Student Science Literacy - Ardian, M. Ferli; Sari, Murni Sapta; Setiowati, Frida Kunti (BIOEDUKASI, 2024)
This research and development aims to produce e-modules based on epub plant structure and development that are valid, practical and effective. The development of teaching materials follows the ADDIE instructional design model. The instruments used were epub-based e-module validation sheets by expert lecturers as well as student response questionnaires and science literacy pretest-posttest scores which were analyzed using the One-Way Ancova test. The results of research and development show the acquisition of a validation score by teaching material experts of 100%, Material experts by 100%, education practitioners by 99%, student response results by 87.05% and efficiency results of 0.013<0.05 so that the use of Epub-based e-modules is effective in the learning process, it can be concluded that EPUB-based e-modules are classified as very valid, very practical and effective as teaching materials that can be used by students.